Production Potential and Some Agronomic Practices of Bambara Groundnut (Vigna subterrenea L). Verdc) Under Rainfed Conditions of South Gedarif Area - Ibrahim, Ibrahim Elsadig; Hassan, Ali ElToum; Elkhair, Jamal (University of Khartoum Journal of Agricultural Sciences, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*174.38px); top: calc(var(--scale-factor)*265.03px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.941714);" role="presentation">Field experiments were executed for two successive seasons <span dir="ltr" style="left: calc(var(--scale-factor)*129.86px); top: calc(var(--scale-factor)*278.83px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.929325);" role="presentation">(2009 and 2010), at the southern area of Gedarif State with the objective <span dir="ltr" style="left: calc(var(--scale-factor)*129.86px); top: calc(var(--scale-factor)*292.63px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.965699);" role="presentation">of studying the influence of sowing date and population density on the <span dir="ltr" style="left: calc(var(--scale-factor)*129.86px); top: calc(var(--scale-factor)*306.43px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.944239);" role="presentation">productivity of a land race Bambara groundnut. Four sowing dates, viz., <span dir="ltr" style="left: calc(var(--scale-factor)*129.86px); top: calc(var(--scale-factor)*320.23px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.89955);" role="presentation">27<span dir="ltr" style="left: calc(var(--scale-factor)*141.86px); top: calc(var(--scale-factor)*317.71px); font-size: calc(var(--scale-factor)*8.04px); font-family: sans-serif; transform: scaleX(0.954549);" role="presentation">th <span dir="ltr" style="left: calc(var(--scale-factor)*153.50px); top: calc(var(--scale-factor)*320.23px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.976723);" role="presentation">of June, 9<span dir="ltr" style="left: calc(var(--scale-factor)*205.01px); top: calc(var(--scale-factor)*317.71px); font-size: calc(var(--scale-factor)*8.04px); font-family: sans-serif; transform: scaleX(0.936367);" role="presentation">th<span dir="ltr" style="left: calc(var(--scale-factor)*211.25px); top: calc(var(--scale-factor)*320.23px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.0134);" role="presentation">, 19<span dir="ltr" style="left: calc(var(--scale-factor)*231.53px); top: calc(var(--scale-factor)*317.71px); font-size: calc(var(--scale-factor)*8.04px); font-family: sans-serif; transform: scaleX(0.936367);" role="presentation">th <span dir="ltr" style="left: calc(var(--scale-factor)*243.05px); top: calc(var(--scale-factor)*320.23px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.941876);" role="presentation">and 27<span dir="ltr" style="left: calc(var(--scale-factor)*277.61px); top: calc(var(--scale-factor)*317.71px); font-size: calc(var(--scale-factor)*8.04px); font-family: sans-serif; transform: scaleX(0.954549);" role="presentation">th <span dir="ltr" style="left: calc(var(--scale-factor)*289.25px); top: calc(var(--scale-factor)*320.23px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.00089);" role="presentation">of July and five combinations of inter- <span dir="ltr" style="left: calc(var(--scale-factor)*129.86px); top: calc(var(--scale-factor)*334.03px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.957355);" role="presentation">row*intra-row spacings, 40cmx30cm, 40x20, 30x30, 30x20 and 20x20, <span dir="ltr" style="left: calc(var(--scale-factor)*129.86px); top: calc(var(--scale-factor)*347.83px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.920594);" role="presentation">were used during both seasons. The data recorded in both seasons were <span dir="ltr" style="left: calc(var(--scale-factor)*129.86px); top: calc(var(--scale-factor)*361.63px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.969384);" role="presentation">plant height, canopy width, 100 seed weight, shelling % and pod yield <span dir="ltr" style="left: calc(var(--scale-factor)*129.86px); top: calc(var(--scale-factor)*375.43px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.899918);" role="presentation">ton/ha. <span dir="ltr" style="left: calc(var(--scale-factor)*171.74px); top: calc(var(--scale-factor)*375.43px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.883879);" role="presentation">Results <span dir="ltr" style="left: calc(var(--scale-factor)*215.98px); top: calc(var(--scale-factor)*375.43px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.881095);" role="presentation">revealed <span dir="ltr" style="left: calc(var(--scale-factor)*265.40px); top: calc(var(--scale-factor)*375.43px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.98622);" role="presentation">highly <span dir="ltr" style="left: calc(var(--scale-factor)*304.95px); top: calc(var(--scale-factor)*375.43px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.948529);" role="presentation">significant <span dir="ltr" style="left: calc(var(--scale-factor)*364.44px); top: calc(var(--scale-factor)*375.43px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.910621);" role="presentation">differences <span dir="ltr" style="left: calc(var(--scale-factor)*426.57px); top: calc(var(--scale-factor)*375.43px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.999572);" role="presentation">in <span dir="ltr" style="left: calc(var(--scale-factor)*444.79px); top: calc(var(--scale-factor)*375.43px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.897692);" role="presentation">most <span dir="ltr" style="left: calc(var(--scale-factor)*477.05px); top: calc(var(--scale-factor)*375.43px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.0104);" role="presentation">of <span dir="ltr" style="left: calc(var(--scale-factor)*129.86px); top: calc(var(--scale-factor)*389.23px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.925076);" role="presentation">measured parameters with respect to sowing date. Early sowing resulted <span dir="ltr" style="left: calc(var(--scale-factor)*129.86px); top: calc(var(--scale-factor)*403.03px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.987069);" role="presentation">in a significantly higher pod yield (4.3 ton/ha) when compared to late <span dir="ltr" style="left: calc(var(--scale-factor)*129.86px); top: calc(var(--scale-factor)*416.85px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.01799);" role="presentation">sowings (i.e. 2.3, 1.3 and 0.94 ton/ha for 9<span dir="ltr" style="left: calc(var(--scale-factor)*357.91px); top: calc(var(--scale-factor)*414.33px); font-size: calc(var(--scale-factor)*8.04px); font-family: sans-serif; transform: scaleX(0.936367);" role="presentation">th<span dir="ltr" style="left: calc(var(--scale-factor)*364.15px); top: calc(var(--scale-factor)*416.85px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.02654);" role="presentation">, 19th and 27<span dir="ltr" style="left: calc(var(--scale-factor)*436.03px); top: calc(var(--scale-factor)*414.33px); font-size: calc(var(--scale-factor)*8.04px); font-family: sans-serif; transform: scaleX(0.936367);" role="presentation">th <span dir="ltr" style="left: calc(var(--scale-factor)*448.39px); top: calc(var(--scale-factor)*416.85px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.04673);" role="presentation">of July, <span dir="ltr" style="left: calc(var(--scale-factor)*129.86px); top: calc(var(--scale-factor)*430.65px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.966741);" role="presentation">respectively). Variable <span dir="ltr" style="left: calc(var(--scale-factor)*250.38px); top: calc(var(--scale-factor)*430.65px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.00184);" role="presentation">plant spacing significantly affected pod <span dir="ltr" style="left: calc(var(--scale-factor)*463.34px); top: calc(var(--scale-factor)*430.65px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.962723);" role="presentation">yield <span dir="ltr" style="left: calc(var(--scale-factor)*129.86px); top: calc(var(--scale-factor)*444.45px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.920756);" role="presentation">during the first season, while no significant variation was observed during <span dir="ltr" style="left: calc(var(--scale-factor)*129.86px); top: calc(var(--scale-factor)*458.25px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.92402);" role="presentation">the second season. Nevertheless, higher yields were obtained with wider <span dir="ltr" style="left: calc(var(--scale-factor)*129.86px); top: calc(var(--scale-factor)*472.05px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.973124);" role="presentation">spacings. Accordingly, the early sowing from late June to early July is <span dir="ltr" style="left: calc(var(--scale-factor)*129.86px); top: calc(var(--scale-factor)*485.85px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.917994);" role="presentation">suggested as optimum sowing date for Bambara groundnut with row-crop <span dir="ltr" style="left: calc(var(--scale-factor)*129.86px); top: calc(var(--scale-factor)*499.65px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.979832);" role="presentation">spacings of 40-30cm inter-row and 30-20cm intra-row for the rain fed <span dir="ltr" style="left: calc(var(--scale-factor)*129.86px); top: calc(var(--scale-factor)*513.45px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.908895);" role="presentation">conditions of south Gedarif area.